Analisis Perilaku Anak Hiperaktif di Sekolah Dasar Terhadap Ekstrakulikuler Karate di Kecamatan Sumedang Selatan - Rahmat, Kintan Rahayu; Muhtar, Tatang; Nur Alif, Muhammad Nur Alif; Setia Lengkana, Anggi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze in more depth the behavior of hyperactive children towards karate extracurricular activities and how karate extracurricular activities can control excess energy in children with hyperactive disorders. This study was conducted using a qualitative case study method. It used 8 participants consisting of 3 hyperactive children, three parents of hyperactive children, one coach, and one karate extracurricular teacher at an elementary school in South Sumedang District. Data was collected using triangulation, which consisted of interviews, field observations, and documentation. Data analysis was carried out with the help of the NVivo 15 Pro application by coding and categorizing important themes as researcher findings. The emergence of the essential conclusions consisting of the behavior of hyperactive children towards karate extracurricular activities, the benefits of karate extracurricular activities, the challenges of parents and coaches in dealing with karate extracurricular activities, and changes in the behavior of hyperactive children after participating in karate extracurricular activities. In conclusion, this study's results provide insight to parents, coaches, educators, and even therapists regarding the benefits of karate extracurricular activities as an effective medium to support the management of excess energy in hyperactive children. Keywords: Children, Hyperactive Children, Karate extracurricular activities